2022
DOI: 10.3390/diagnostics12061499
|View full text |Cite
|
Sign up to set email alerts
|

Optics and Utility of Low-Cost Smartphone-Based Portable Digital Fundus Camera System for Screening of Retinal Diseases

Abstract: Purpose: To describe optical principles and utility of inexpensive, portable, non-contact digital smartphone-based camera for the acquisition of fundus photographs for the evaluation of retinal disorders. Methods: The digital camera has a high-quality glass 25 D condensing lens attached to a 21.4-megapixel smartphone camera. The white-emitting LED light of the smartphone at low illumination levels is used to visualize the fundus and limit source reflection. The camera captures a high-definition fundus (5344 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Chalam et al. showed that fundic images captured with the Volk iNview (i.e., an older version of the Volk camera used in the current work) were also comparable with those acquired simultaneously with a traditional fundus camera 15 …”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Chalam et al. showed that fundic images captured with the Volk iNview (i.e., an older version of the Volk camera used in the current work) were also comparable with those acquired simultaneously with a traditional fundus camera 15 …”
Section: Discussionmentioning
confidence: 55%
“…14 Chalam et al showed that fundic images captured with the Volk iNview (i.e., an older version of the Volk camera used in the current work) were also comparable with those acquired simultaneously with a traditional fundus camera. 15 Smartphone-based fundus imaging has tremendous potential to revive the 'dying art' of ocular fundoscopy. 3 Similar to human physicians, 3 veterinarians and veterinary students often lack confidence in ophthalmoscopy, not only in the technical skill but also in the ability to interpret findings and detect potential abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The microfluidic chips can also be used for filtration and sample purification, which can result in higher accuracy [129,161,162]. Another crucial challenge at present is the miniaturization of these assay platforms and detection systems in order to expand their utility, particularly with regard to wearable devices (band, rings, patches, watches, glasses, shoes) [163][164][165][166][167]. Presently, wearable devices are very popular, as they make it possible to monitor a person's vitals in real time [168,169].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in [ 43 ], the authors employ a white light-emitting diode (LED) confocal device instead of the traditional fundus camera to overcome the frequent red-channel oversaturation. In another study [ 44 ], a simple smartphone camera (21.4-megapixel) is shown to be a useful alternative to conventional fundus camera equipment, increasing portability, ease of use, and dissemination. Furthermore, in [ 45 ], a red–green–blue (RGB) imaging regime is employed to extract label-free information about the oxygen saturation (SO 2 ) and hemoglobin concentration in the fundus, an option that could facilitate early detection of disease.…”
Section: Diabetic Retinopathymentioning
confidence: 99%